The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1978
DOI: 10.1271/bbb1961.42.1037
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, structures and biological activities of colletotrichins, phytotoxic substances from Colletotrichum nicotianae.

Abstract: From the phytopathogenic fungus, Colletotrichum nicotianae, three phytotoxic substances have been isolated and named colletotrichin, colletotrichins B and C (1, 2 and 3). The struc tures of these compounds have been elucidated from the physical and chemical evidence. When applied on the tobacco leaves, colletotrichins induced the symptom similar to that of the tobacco anthracnose caused by C. nicotianae. The compounds were also toxic to the lettuce and rice seedlings. with C. nicotianae. 1 was identified to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 0 publications
3
16
0
1
Order By: Relevance
“…1a) associated with necrosis suggests the involvement of phenolic compounds and their oxidation products similar to symptoms observed in sugarcane plants infected with the red rot pathogen (Rao et al 1968). Similar influences of toxins on different crops have been reported by Gohbara et al (1978) on lettuce, Jin et al (1996) on soybean, Boonchitsirikul et al (1997) and Narong et al (1998) on rice and Prasad and Naik (2000) on sugarcane. Growth inhibition of sugarcane calli by the PCF provides a positive selection system in which susceptible cells presumably die and/or grow slowly, while more resistant cells proliferate faster.…”
Section: Discussionsupporting
confidence: 71%
“…1a) associated with necrosis suggests the involvement of phenolic compounds and their oxidation products similar to symptoms observed in sugarcane plants infected with the red rot pathogen (Rao et al 1968). Similar influences of toxins on different crops have been reported by Gohbara et al (1978) on lettuce, Jin et al (1996) on soybean, Boonchitsirikul et al (1997) and Narong et al (1998) on rice and Prasad and Naik (2000) on sugarcane. Growth inhibition of sugarcane calli by the PCF provides a positive selection system in which susceptible cells presumably die and/or grow slowly, while more resistant cells proliferate faster.…”
Section: Discussionsupporting
confidence: 71%
“…(Sahni et al, 1974), C. musae (Berk. and M. A. Curtis) (Chen, 1968) and C. nicotianae (Gohbara et al, 1978;Duke et al, 1992) have also been shown to produce phytotoxins that are involved in the disease process. Colletotrichum gloeosporioides produces phytotoxic metabolites in vitro and in vivo in Citrus aurantifolia L. (Sharma and Sharma, 1969;Sahni et al, 1974), northern jointvetch (Aeschynomene virginica L.) (Walker and Templeton, 1978), olive (Olea europaea L.) (Ballio et al, 1969;Bosquet et al, 1971) and Stylosanthes scabra L. (Szabados et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Colletotrichin, a norditerpene-pyrone, is a non-host-specific phytotoxin produced by species of Colletotrichum (Gohbara et al, 1977;Gohbara et al, 1978). Originally called acetylcolletotrichin (Grove et al, 1966), it is related to other analogs, colletotrichin B and colletotrichin C, which are precursors of colletotrichin .…”
Section: Colletotrichum Speciesmentioning
confidence: 99%